1998
DOI: 10.1159/000017346
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Central Cholinergic Deficit in Congenital Ornithine Transcarbamylase Deficiency

Abstract: Congenital ornithine transcarbamylase (OTC) deficiency is the most common inborn error of urea cycle enzymes in humans. A large percentage of survivors of neonatal OTC deficiency suffer severe developmental disorders, including seizures, mental retardation and cerebral palsy. Neuropathological studies reveal ventricular enlargement, cerebral atrophy and delayed myelination, as well as Alzheimer type II astrocytosis. Using the sparse-fur (spf) mouse model of congenital OTC deficiency, studies of central choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The degree of cholinergic cell loss in the central nervous system relates to the level of neuropathologic alteration, memory impairment and cognitive lesion. [206][207][208][209] AChE and choline levels in patients' cerebrospinal fluid have a close relationship to the severity of dementia. [210][211][212][213] Recent studies have shown that HupA possesses additional pharmacological actions other than affecting the hydrolysis of synaptic ACh described directly above.…”
Section: Neural Cell Protectionmentioning
confidence: 99%
“…The degree of cholinergic cell loss in the central nervous system relates to the level of neuropathologic alteration, memory impairment and cognitive lesion. [206][207][208][209] AChE and choline levels in patients' cerebrospinal fluid have a close relationship to the severity of dementia. [210][211][212][213] Recent studies have shown that HupA possesses additional pharmacological actions other than affecting the hydrolysis of synaptic ACh described directly above.…”
Section: Neural Cell Protectionmentioning
confidence: 99%
“…This can lead to impaired cerebral energy metabolism. Further explanations may relate to the toxic effects of metabolites and NMDA (glutamate) receptormediated excitotoxicity caused by energy depletion ("slow onset excitotoxicity") (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for osmotic effects of glutamine generated in astrocytes as a consequence of ammonia removal leading to brain swelling (6). Another explanation may be alterations of serotonin synthesis and turnover in brain (3,4). Increased glutamine synthesis in brain may have deleterious effects, including a role in the stimulation of aromatic amino acid transport across the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the only available animal model of congenital hyperammonemia was the sparse-fur ( spf ) mouse carrying a point mutation in the ornithine transcarbamoylase (OTC) gene1516. Spf mice have blood ammonia levels that are 2–3fold higher than normal; they show cerebral atrophy, significant alterations in neurotransmitter systems, behavioral abnormalities, and a decreased life span161718192021. As OTC is central for the mitochondrial portion of the urea cycle, it is not surprising that spf mice also show adaptive alterations in other mitochondrial enzyme activities and deficits in energy metabolism making a clear deduction of findings from mere hyperammonemia rather difficult.…”
mentioning
confidence: 99%